2018
DOI: 10.1016/j.cub.2018.05.046
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Ecosystem Services from Giant Panda Reserves

Abstract: Ecosystem services (the benefits to humans from ecosystems) are estimated globally at $125 trillion/year [1, 2]. Similar assessments at national and regional scales show how these services support our lives [3]. All valuations recognize the role of biodiversity, which continues to decrease around the world in maintaining these services [4, 5]. The giant panda epitomizes the flagship species [6]. Its unrivalled public appeal translates into support for conservation funding and policy, including a tax on foreign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(47 citation statements)
references
References 49 publications
1
45
0
1
Order By: Relevance
“…Thanks to the low‐latitude and sky‐island features, approximately 40% of the vascular plant and 50% of the mammal species in China are distributed in the MSCAM, a large portion of which are endemic to that region. Nevertheless, except for a handful flagship species such as the giant panda, which have attracted popular attention and scientific interest (Wei et al, ), most of the unique organisms have been overlooked. Recent studies have shown that species diversity in this area is highly underestimated (He et al, ), and the area has become a significant hotspot for the discovery of new species (e.g., Cheng et al, ; Fan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the low‐latitude and sky‐island features, approximately 40% of the vascular plant and 50% of the mammal species in China are distributed in the MSCAM, a large portion of which are endemic to that region. Nevertheless, except for a handful flagship species such as the giant panda, which have attracted popular attention and scientific interest (Wei et al, ), most of the unique organisms have been overlooked. Recent studies have shown that species diversity in this area is highly underestimated (He et al, ), and the area has become a significant hotspot for the discovery of new species (e.g., Cheng et al, ; Fan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These corridors make the spatial pattern of urban ecosystems holistic and internal. The ecological corridor can prevent soil erosion, improve carbon storage, and contribute to biodiversity conservation and ecosystem stability [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the estimation of ESVs can make a vital contribution to ecological protection and sustainable development [6,7]. ESV assessments at the national, regional, basin, and even single ecosystem levels can show how these services support our lives and how we utilize natural resources and ecological products [7,8]. The valuation methods now available are highly developed and can be mainly divided into behavioral (revealed preference) methods and attitudinal (stated preference) methods [4].…”
Section: Introductionmentioning
confidence: 99%